Textured Renyl Entropy for Image Thresholding - Abu Shareha, Ahmad Adel; Rajeswari, Mandava; Ramachandram, Dhanesh (2008)
This paper introduces Textured Renyi Entropy for image thresholding based on a novel combination mechanism.